Developing collaborative best practices for digital humanities data collection: A case study. Issue 2 (2nd October 2017) - Di Cresce, Rachel; King, Julia
ABSTRACT: This case study explores the data management practices of medieval manuscript scholars working on the Digital Tools for Manuscript Study project at the University of Toronto. We chose this user group, despite their incredibly domain-specific praxis, since the data challenges they face while doing digital humanities work are representative of the wider community. Our goal is to rethink how librarians can best assist researchers within a digital humanities (DH)-centered environment. This article first explores how data are conceived in the DH context and what insights can be drawn for data management. Next, focus shifts to the key characteristics of data collection and postprocessing activities carried out by manuscript scholars during repository visits. Parallels are drawn between manuscript scholar practices and those of other humanities disciplines. Finally, the implications for information professionals are explored and best practices for assisting digital humanists defined. In particular, community engagement in the process is stressed throughout, as it is the authors' belief that it is necessary for success. The best practices are in no way exhaustive, and they are intended to be broadly applicable to a range of disciplines within the digital humanities and to librarians. Future work will involve validating a new data management approach informed by this study by testing in the field.